Environmental Protection as Market Pathology?: Carbon Trading and the Dialectics of the 'Double Movement'. (December 2014) - Carton, Wim
Polanyi's concept of the 'double movement' is frequently interpreted as the opposition between the problematic and unsustainable dynamics of the market and the benign and normatively desirable reaction against this by 'society'. This paper questions this dualistic interpretation of the double movement and undertakes a problematization of the Polanyian idea of social and environmental protection. It does this by revisiting the concept of the double movement in light of the recent proliferation of market-based mechanisms for environmental regulation. Through an exploration of the different interpretations of Polanyi's work, the paper presents a dialectical reading of the double movement that conceptualizes the idea of social protection within a broader capitalist framework. This is then illustrated with the case of emissions trading as a particular form of environmental protection. Carbon trading as a mitigation strategy, it is argued, corresponds to the Polanyian idea of 'social protection' in that its protective potential to reduce emissions is itself constrained by the socioeconomic framework within which it operates. This in turn points to the need for a critique of climate mitigation efforts that goes beyond a focus on current problems with emissions trading schemes.